DEVELOPMENT OF A PLANT-BASED BURGER WITH TARWI FLOUR (Lupinus mutabilis), BLACK BEANS (Phaseolus vulgaris), AND CUSHURO FLOUR (Nostoc sphaericum s.p.) - Valderrama Ll., Diego Carlos (2025)
The trend in the consumption of plant-based products is increasing due to the growing concern about the sustainability and environmental effects of meat product production. In this context, a plant-based hamburger with a high protein content and a balanced profile of essential amino acids was made, combining tarwi flour (Lupinus mutabilis), black bean (Phaseolus vulgaris) and cushuro (Nostoc sphaericum). Tarwi is an Andean legume rich in protein (40-50%) and healthy fats (20%), while black beans are an important source of fiber and minerals. The cushuro, a high Andean cyanobacterium, has a high protein content and minerals such as iron and calcium. For the formulation of the plant-based hamburger, tarwi flour (45%), cushuro flour (2.33%), black beans (8.77%), carrots (3%), eggs (36%), mara salt (0.85%), oregano powder (0.75%), paprika powder (1.4%), ground garlic (0.9%) and onion powder (1%) were mixed. The results showed that the optimal sample (OM) presented 30.48% protein, 36.19% moisture, 22.06% fat and 8.91% carbohydrates, with a balanced amino acid profile, highlighting glutamic acid (196.16 ± 4.77 mg/g protein), arginine (145.91 ± 4.75 mg/g protein), aspartic acid (83.00 ± 4.52 mg/g protein). In addition, an antioxidant activity of 1502.19 μg trolox/g was obtained, and in the sensory evaluation the OM reached an acceptability of 86.67%, standing out in flavor, texture and appearance compared to the control sample, which demonstrates its potential as a sustainable and nutritious protein alternative.